Clinical Value of Pharmacogenomic Testing in a Patient Receiving FOLFIRINOX for Pancreatic Adenocarcinoma - Velez-Velez, Lisa M.; Hughes, Caren L.; Kasi, Pashtoon Murtaza (Frontiers in Pharmacology, 2018)
Pharmacogenomic testing may have clinical value in the treatment of patients with gastrointestinal malignancies such as colorectal and pancreatic cancer. These types of cancer are often treated with combination chemotherapy regimens. These regimens can lead to severe adverse effects in patients with diminished drug tolerability potentially due to certain genetic variants in the enzymes involved in the metabolism of the chemotherapies. Genetic variants resulting in decreased enzymatic activity of uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) and dihydropyrimidine dehydrogenase (DPD) are known to increase irinotecan and 5-fluorouracil-related toxicity, respectively. We report a case of a patient with pancreatic adenocarcinoma who was found to be not only homozygous for the UGT1A1∗28 allele, but also heterozygous for a DPYD variant through pharmacogenomic testing. Potentially severe adverse effects were prevented in this patient’s case by implementing preemptive dose reductions. On the basis of the significant implications of chemotherapy-related toxicity in this and other similar cases, we report on the clinical value of integrating pharmacogenomic testing into clinical practice to allow for preemptive and/or point-of-care dose reductions in patients potentially at risk for increased toxicity. This is even more important in an era where combinatorial triplet chemotherapies are increasingly being used.